A novel protocol for the establishment of in vitro intrauterine adhesions model - Hosseini, MirMohammadReza; Rashidan, Kimiya; Gandomkar, Hadis; Faraji, Ahmadreza; Mosaffa, Nariman; Ghanbarian, Hossein; Ghaffarikhaligh, Sahar; Hashemi, Seyed Mahmoud (Student Research in Translational Medicine, 2023)
Background and aim: Intrauterine adhesions (IUAs), also known as Asherman's syndrome, is a prevalent gynecological condition that presents with various clinical manifestations, including atypical menstrual patterns, pelvic discomfort, reduced endometrial thickness, repeated pregnancy loss, and potential infertility. Despite advancements in therapy, the successful pregnancy rate remains low, especially in severe cases, posing significant therapeutic challenges and poor prognoses. Therefore, extensive research is essential to understand the underlying mechanisms of IUAs and develop effective therapeutic interventions. Materials and Methods: This study introduces a novel method of incubating co-culture of stem cells and intraperitoneal macrophages with hydrogen peroxide (H2O2) and scratch wound to mimic impaired endometrial stromal cells, considering the regenerative properties of macrophages, and prominent leukocytes in the endometrium. The objective was to examine the co-culture endometrial stem cells (EnSCs) of the human uterus and intraperitoneal macrophages as an in vitro model for IUAs. The aim was to establish a physiologically relevant model that replicates the complex cellular interactions and microenvironment observed in the endometrium during IUAs development and investigate the influence of macrophages on the response of stem cells to H2O2. Results: The study involved culturing and preparing EnSCs in a 24-well plate, while peritoneal macrophages were isolated through lavage in mice. Four experimental groups were established: EnSCs alone (group A), EnSCs treated with H2O2 (group B), EnSCs co-cultured with macrophages (group C), and EnSCs co-cultured with macrophages treated with H2O2 (group D). In all groups, the wound was mimicked by a sterile crystal tip. Cell viability was assessed using the MTT test, measuring the reduction of tetrazolium salt to formazan crystals. Nitric oxide (NO) production was measured using the Griess reaction, and cell migration was evaluated through a scratch wound healing assay. Statistical analysis utilized Student's t-test or one-way ANOVA, with GraphPad Prism version 6 software, considering results with p< 0.05 as statistically significant. Conclusion: The findings indicated that H2O2 treatment had a negative impact on EnSCs viability, but co-culturing with macrophages provided a protective effect. Moreover, H2O2 treatment led to increased NO levels, suggesting macrophage activation against oxidative stress. Interestingly, H2O2 treatment promoted cell migration in both EnSCs alone and the co-culture, while macrophages inhibited migration. These results underscore the significance of the interaction between EnSCs and macrophages in understanding IUAs and developing effective treatments Keywords: Intrauterine adhesion; Macrophages; Endometrial Stem cell; in vitro; Scratch wound